Developing educators for the digital age : a framework for capturing knowledge in action - Breen, Paul, 1971- (University of Westminster Press, 2018)
"Evaluating skills and knowledge capture lies at the cutting edge of contemporary higher education where there is a drive towards increasing evaluation of classroom performance and use of digital technologies in pedagogy. Developing Educators for the Digital Age is a book that provides a narrative account of teacher development geared towards the further usage of technologies (including iPads, MOOCs and whiteboards) in the classroom presented via the histories and observation of a diverse group of teachers engaged in the multiple dimensions of their profession."--Publisher's website